The Influence of Brand Image on Brand Loyalty through Brand Love: A Case Study on the Panasonic Brand - Nilowardono, Sengguruh; Artaya, I Putu; Kamisutara, Made; Arimbawa, I Gede (LPPM of NAROTAMA UNIVERSITY, 2024)
Understanding the factors that influence brand loyalty is crucial because it enables businesses to devise effective strategies to retain customers, enhance customer satisfaction, and ensure long-term profitability. This study aims to examine the influence of brand image on brand loyalty through brand love among consumers of Panasonic electronic products in Surabaya. The research employs a quantitative approach with the participation of 96 respondents. Structural equation modeling analysis is used as the analytical technique. The research results indicate that brand image influences brand loyalty for Panasonic electronic products; in other words, the better the brand image, the higher the brand loyalty. Furthermore, brand image affects brand love, meaning the better the brand image, the greater the increase in brand love. It was also found that brand love influences brand loyalty, meaning that an increase in brand love leads to an increase in brand loyalty. This study also reveals that brand love mediates the effect of brand image on brand loyalty for the Panasonic electronic product brand. Understanding the influence of brand image on brand loyalty through brand love for Panasonic electronic products has practical implications that can assist in managerial decision-making, especially in brand management. It will consider factors that can enhance brand love, given that it mediates the influence of brand image on brand loyalty.